Peningkatan Minat Belajar Siswa melalui Strategi Inkuiri di Era Digitalisasi - A. Supu, Mohammad Hambali; Hadi, Agustinus Sutriyanto; Sukoco, Sukoco (Journal of Democratia; Vol 4 No 2 (2025): Jurnal Democratia : Pendidikan Pancasila dan Kewarganegaraan, Moral, Karakter, dan Hukum, 2025)
Development of interest in learning is a process that aims to increase one's motivation and interest in learning. This process involves creating a positive learning environment, using effective learning strategies and providing appropriate stimuli to maintain interest in learning and motivation in learning. Strategy is a plan or planned steps to achieve certain goals or objectives. Strategy involves choosing the right course of action and setting up available resources to achieve the desired result. Strategies can be used in a variety of contexts, whether personal, business, organizational or educational. According to the source, research data is classified as primary and secondary data. Primary data is data that is directly obtained from research subjects, namely testimonies from predetermined informants. For example, in the form of words and actions of people who were observed or interviewed, are the main source of data, namely recorded through written notes or through audio recordings/audio tapes, taking photographs. Secondary data is data that is not obtained directly from research subjects so that it is not limited by space and time, for example written sources in the form of books and scientific magazines to explore the condition of individuals or communities where research is carried out. Photos produce descriptive data that is quite valuable and are often used to examine subjective aspects and the results are often analyzed inductively. The results of this study are that increasing the learning interest of SMPIT ADA students through inquiry strategies in the digitalization era is carried out in various ways starting from the discussion process carried out by the school principal with teachers regarding the application of inquiry strategies using digital media, guidance on the application of inquiry methods to teachers, and the process of observing changes in students' attitudes towards enthusiasm in learning. As for the obstacles faced, the lack of digital media facilities, the lack of cooperation between teachers and students' families, and the lack of interaction with students regarding student personalities.